Mini Riset: Implementasi Metode Pembelajaran Anak Tuna Netra di SLB Negeri 1 Kulon Progo - Rahma Dini, Avivah; Ulil Jannah; Difa’ul Husna (Jurnal Multidisiplin Indonesia, 2023)
The aim of this research is to determine the learning methods used by educators in teaching children with special needs who are blind at SLB Negeri 1 Kulon Progo. Blindness itself is a condition where a person has limited vision, therefore to obtain information they use the senses of hearing and touch. The method used in this research is a descriptive qualitative method, in which the researcher collects information or sources using books, journals and other scientific works related to the topic raised. Then the researchers collected data by conducting interviews and direct observations on Monday 23 October 2023 by one of the teachers of blind children at SLB Negeri 1 Kulon Progo so that the data needed was more valid. The results of the discussion in this research are that there are various learning methods used by children with special needs who are blind at SLB Negeri 1 Kulon Progo, including the following; lecture, audio, practical and tactile (touch) methods. However, in implementing this learning method there are still various obstacles felt by the teachers at SLB Negeri 1 Kulon Progo.